Napak Tilas Perkembangan Pemikiran tentang Pembangunan - A.B. Christono (Bina Ekonomi, 1999)
Development Economics is a science that does not finish yet, like International Economics or Monetary Economics, as universal formula. It still needs elaborations in many discussions to develop it. This paper will be discussing of how Development Economics develops in a dialectical process to become a science that more acceptable and aplicable in the most underdeveloped countries.